Microwave hydrodiffusion and gravity: a green extraction technology for phenylethyl isothiocyanate from watercress by-products - Sousa, Ana Sofia (2025)
Watercress is a cruciferous vegetable and the primary natural source of phenylethyl isothiocyanate (PEITC), a powerful health-promoting agent. Conventional extraction of PEITC relies on harmful solvents, which limits sustainability. This study introduces a novel, solvent-free method—microwave hydrodiffusion and gravity (MHG)—to extract PEITC from watercress by-products (WCBP). Results showed that freezing WCBP is fundamental for effective PEITC extraction via MHG. Using a three-level factorial experimental design, optimal MHG extraction conditions were determined (microwave power: 1.91 W g -1 ; extraction time: 29 min), yielding a PEITC content of 1818.26 μg g -1 WCBP (dry basis), along with extracts rich in polyphenols and possessing antioxidant properties. This work demonstrates that MHG is a sustainable method for extracting isothiocyanates, supporting a zero-waste approach since the clean residue from the extraction process can be reused to obtain new ingredients, thus enhancing resource efficiency and promoting a circular economy in the agro-food industry.